1979
DOI: 10.1002/j.1537-2197.1979.tb06285.x
|View full text |Cite
|
Sign up to set email alerts
|

Trichome Morphology as an Indicator of High Rubber Bearing Guayule (Parthenium Argentatum Gray) Plants in Native Populations

Abstract: Parthenium argentatum Gray (guayule) and P. incanum (mariola) grow in close associations in their native habitat of Mexico. Variation in rubber concentration and morphology of guayule has been known for a long time. Studies of over 75 native guayule plants indicated the presence of at least three prominent forms of guayule plants. Group I guayule plants have oblanceolate leaves and leaf margins are entire to two‐toothed. T‐shaped leaf trichomes are with centrally attached stalk and cap cell with two blunt ends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
3

Year Published

1982
1982
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
1
6
3
Order By: Relevance
“…Nonetheless, the ratio of blunt arms to pointed arms was never significantly correlated with rubber content (Table 4). This is in contrast to the conclusions of Mehta et aL (1979), who found a positive correlation between arm ratio and rubber content in the native guayule population, with arm ratio decreasing as rubber content increased.…”
Section: Resultscontrasting
confidence: 86%
See 4 more Smart Citations
“…Nonetheless, the ratio of blunt arms to pointed arms was never significantly correlated with rubber content (Table 4). This is in contrast to the conclusions of Mehta et aL (1979), who found a positive correlation between arm ratio and rubber content in the native guayule population, with arm ratio decreasing as rubber content increased.…”
Section: Resultscontrasting
confidence: 86%
“…Our results contradict those of Mehta et al (1979), who reported that these characteristics could serve as indicators of the level of rubber production in guayule. Mehta et aL (1979) had reported that these characteristics could be modified by changes in climate, soil properties, or genetic makeup of the plant (Mehta et at., 1979). In the current study, only a limited number of plants (10 to 15 per variety) were available for study.…”
Section: Resultscontrasting
confidence: 85%
See 3 more Smart Citations